(untitled) (Південний архів (історичні науки), 2025)
The purpose of the study is to identify the forms and mechanisms of participation of the Orthodox clergy of the Ukrainian SSR in the training of future seminarians in the second half of the twentieth century, given the restrictions on religious education and the anti- religious policy of the Soviet government. The research methods were problem-chronological, comparative-historical, descriptive, reconstructive, and specific analysis of historical sources. Research results. The participation of the Orthodox clergy of the Ukrainian SSR in the training of future seminarians in the second half of the twentieth century was analysed against the background of restrictions on religious education and the anti-religious policy of the Soviet government. Legal, semi-legal and illegal forms of involving young people in spiritual life were revealed, including liturgical practice, individual mentoring and informal religious education. The role of priests as carriers of religious continuity, spiritual mentors and mediators in forming pastoral personnel was traced. It was found that the informal activity of the clergy in preparing young people for pastoral ministry became a form of latent resistance to the Soviet anti-religious policy and a prerequisite for the religious revival of the late 1980s. Conclusions. The Orthodox clergy in the Ukrainian SSR in the second half of the 20th century played not only a religious and ritual role, but also an educational and upbringing role, taking on the functions of spiritual guidance and initial theological education under strict restrictions. Forming informal mechanisms for training future pastors, parish priests developed a range of adaptation practices that combined participation in divine services, religious education in families, individual conversations, providing access to spiritual literature, and support for applicants at all stages of entering seminaries. These processes acquired both a spontaneous and systemic character within church communities. A feature of the identified practices was their deep roots in the local religious environment and dependence on the personal initiative of the priest, which indicates the human factor’s significant role in preserving and transmitting religious tradition. The presence of hidden models of spiritual training and care indicates the viability of the church community even in conditions of ideological control and persecution.